Coseismic Stability Assessment of a Damaged Underground Ammunition Storage Chamber Through Ambient Vibration Recordings and Numerical Modelling - Glueer, Franziska; Häusler, Mauro; Gischig, Valentin; Fäh, Donat (Frontiers in Earth Science, 2021)
In the past decade, ambient vibration measurements found numerous applications on unstable rock slopes and developed into a powerful tool for site characterization of slope instabilities. In this study, for the first time ambient vibration measurements were applied to a rock mass strongly disturbed and damaged by subsurface explosions. The site above the ammunition storage chamber at Mitholz (Switzerland) is especially interesting because the subsurface below the seismic array is well known regarding geology, the location of the caverns, and the degree of degradation caused by the subsurface explosions in 1947 of around 40 t TNT of ammunition. Measurement data were analyzed using current state-of-the-art seismic single-station and array methods, focusing on surface-wave dispersion analysis, wave field polarization, wave amplification using site-to-reference spectral ratios and analysis of normal mode behavior. The results allow for calibrating the elastic properties of a 2D numerical rock mechanical model that was used to simulate the stability of the disturbed rock mass during seismic loading. Therefore, ambient vibration measurements can contribute not only to a better understanding of the subsurface, but also for the assessment of earthquake risk.